A layer-by-layer assembly label-free electrochemical immunosensor for the detection of microcystin-LR based on CHIT/PAMAM dendrimer/silver nanocubes. Issue 3 (19th February 2016) - Fu, Xuewen; Zhao, Chunling; Liu, Xiaohai; Zhao, Jinhang; Niu, Xiaofang; Zheng, Li; Yang, Yunhui
ABSTRACT: Utilising the affinity and high combination ability between silver nanocubes and amino group (–NH2 ), a novel electrochemical immunosensor was constructed for the ultrasensitive detection of microcystin-LR (MC-LR) based on G4-polyamidoamine (PAMAM) dendrimer and Ag nanocubes as immobilised substrate of anti-MC-LR. G4-PAMAM dendrimers were covalently bound on the chitosan (CHIT) – modified electrode by glutaraldehyde (GA), providing abundant amino groups to absorb much more Ag nanocubes comparing without using PAMAM. Subsequently, antibodies of MC-LR were immobilised with highly dense through Ag-NH2 . K3 Fe(CN)6 /K4 Fe(CN)6 was used as electroactive redox probe. Ag nanocubes/PAMAM can enhance the antibody loading amount, which would bind more MC-LR and hinder the electron transfer of K3 Fe(CN)6 /K4 Fe(CN)6 . Differential pulse voltammetry (DPV) was employed to evaluate the analytical performance of the fabricated signal-off immunosensor. The response current had negative correlation with the concentration of MC-LR. The linear range covered was from 0.05 ng/mL to 25 μg/mL with detection limit (DL) of 0.017 ng/mL at 3σ. The proposed approach showed high specificity for the detection of MC-LR, with acceptable reproducibility, stability and reliability. Compared with the enzyme-linked immunoassay (ELISA) method by analyzing real water samples from Dian Lake, this immunosensor revealed acceptable accuracy with a relative error of 12.7%, indicating a potential alternative method for MC-LR detection in water sample.